characteristics of patients of gout arthritis in the work area of tumori village west gunungsitoli village in 2021 - Mei Frans Syah Putra Harapan Hati Hulu (Sean Institute, 2022)
Gout arthritis is a metabolic disease caused by excess levels of uric acid compounds in the body, either due to excess production, insufficient elimination, or increased purine intake. Method: This type of research is descriptive with a total sampling technique of sampling, the number of samples is 40 people. The instrument used in this study was a questionnaire which was distributed to respondents who suffered from Gout Arthritis. Results: The results showed that there were more patients with Gout Arthritis in the 56-65 years age group (35.0%). The majority of Gout Arthritis sufferers are female (70.0 %). Most patients with Gout Arthritis have a junior high school education/equivalent (32.5%). Patients with Gout Arthritis who have a history of family/genetic disease (65.0%).